The psychology of personal constructs. - Kelly, George, 1905-1967 (Routledge in association with the Centre for Personal Construct Psychology, 1991)
Unavailable for many years this is a reissue of George Kelly's classic work. It is the bible of personal construct psychology written by its founder. The first volume presents the theory of personal construct psychology.